PENURUNAN BILIRUBIN MENINGKATKAN OKSIDASI LIPOPROTEIN A PADA NEFROPATI DIABETIK - Meutia Atika Faradilla; Yahwardiah Siregar; Darwin Dalimunthe (Universitas Syiah Kuala, 2017)
ABSTRACT. Diabetic nephropathy is the most common complication of microvascular disease due to diabetes and the third leading cause of renal failure to the end stage. One of the causes of diabetic nephrophaty progression is increase oxidants by lipoprotein a. Bilirubin is a lipophilic endogenous antioxidant that can prevent oxidant effect. This study aims to determine the correlation between bilirubin levels and lipoprotein a in patients with diabetic nephropathy. This research is a case control study with consecutive sampling technique. The subjects were divided into two groups, 25 subjects in the diabetic nephropathy group and 25 subjects in the type 2 diabetes mellitus group without nephropathy. Spearman correlation was used to assess the correlation between bilirubin and lipoprotein a and the mann-whitney test to assess the ratio of bilirubin and lipoprotein a levels in both groups. Antioxidant effect of bilirubin significantly negative correlated with lipoprotein a in the diabetic nephropathy group (r = -0.734; p = 0.000) and also significantly negative correlated in the group of type 2 DM without nephropathy (r = -0.476; p = 0.016). Bilirubin levels in diabetic nephropathy were lower when compared with the group of type 2 DM without nephropathy (OR = 1.3, 95%; CI = 0.23-10.3) whereas lipoprotein a in the diabetic nephropathy group was higher when compared to the type 2 DM group without nephropathy ( OR = 2.8; 95%; CI = 1.84-12.07). Lipoprotein a is a more important risk factor for diabetic nephropathy. Low levels of bilirubin can increase oxidant effect of lipoprotein a and lipoprotein a play a role in progressivity of diabetic nephrophaty.